مفهوم المراهقة في الاسلام: دراسة تحليلية: The Concept of Adolescence in Islam: An Analytical Study - Nezar Al Qahtani; Merah Souad; Tahraoui Ramdane (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص يهدف هذا البحث التحليلي الى التعرف على مفهوم المراهقة في الاسلام و توضيح استعمالاته وكل ما يترتب عن ذلك من حقوق وواجبات، اضافة إلى التعرف على الإستراتيجيات التربوية الاسلامية للتعامل مع هذه الفئة العمرية، و خدمة لهذه الأهداف تم استخدم المنهج التاريخي الاستقرائي الذي يعتمد على طريقة المراجعة الممنهجة (Systematic Review) ، حيث قام الباحثون بجمع وتحليل المعلومات ذات الصلة من نصوص السنة النبوية، حيث قام الباحثون بدراسة النصوص النبوية التي تطرح مسألة المراهقة من خلال كتب شروح الحديث المعتمدة كفتح الباري لابن حجر و شرح النووي على صحيح مسلم و غيرهما، و كذلك كتب المذاهب الفقهية المعتمدة، و ذلك للوصول إلى النظرة الإسلامية لمفهوم المراهقة، و كيفية التعامل مع هذه المرحلة. ولقد توصلت نتائج هذه الدراسة -على خلاف ما هو شائع من أنه مصطلح دخيل على الاسلام- الى أن مصطلح المراهقة مصطلح أصيل و مذكور بطريقة صريحة في السنة النبوية كما دونتها كتب الحديث المعتمدة، و كتب المذاهب الفقهية المختلفة. ولقد استخدم هذا المصطلح لوصف الفئة العمرية التي تمر بمرحلة انتقالية بين الطفولة إلى الرشد، و هو ما بين عشر إلى خمسة عشرة سنة كما توصلت إليه الدراسة، أما عن طريقة التعامل مع المراهقين وتربيتهم في الاسلام فقد توصلت الدراسة إلى أن مرحلة المراهقة هي مرحلة تمكين للأبناء لكي يكونوا أفراداً راشدين قادرين على القيام بالأدوار المطلوبة منهم في المجتمع، ويتوقع أن تفيد هذه الدراسة الباحثين المهتمين بالمراهقة وكل من له صلة بتربية المراهقين عموما والمراهقين المسلمين خصوصا وذلك عن طريق التعامل مع هذه الفئة كفئة تستحق التمكين و الدعم و التطوير من المجتمع، و ليس فئة تمر بالعديد من الاضطرابات النفسية التي بسببها يتم التبرير لبعض السلوكيات الغير مقبولة منها، و كذلك من خلال الاعتماد على المنهج الإسلامي التربوي في تعزيز السلوكيات الإيجابية لهذه الفئة و تصحيح سلوكياتهم السلبية، كما ستكون هذه الدراسة ممهدة لدراسات مستقبلية أخرى تضع نماذج تربوية تعتمد على المنهج الإسلامي في التعامل مع المراهقين، و تقوم بالعمل على تطبيقه في الميدان التربوي. الكلمات المفتاحية: المراهقة، السنة النبوية، التمكين، الارشاد، التربية الإسلامية Abstract This analytical research aims to identify the concept of adolescence in Islam and clarify its uses and all the consequent rights and duties, in addition to identifying Islamic educational strategies to deal with this age group, and in service of these goals was used the historical inductive approach based on systematic review method, The researchers collected and analyzed the relevant information from the texts of the Prophet's Sunnah, where the researchers studied prophetic texts that raised the issue of adolescence through the books of hadith commentaries adopted such as Fatah al-Bari to ibn Hajar and shareh Al Naoaoi on a Muslim and other books, as well as books of adopted jurisprudence doctrines, in order to reach the Islamic view of the concept of adolescence, and how to deal with this stage. The results of this study, contrary to what is common in terms of alien to Islam, have concluded that the term adolescence is an authentic term and is explicitly mentioned in the Prophet's Sunnah, as written by the hadith books, and the books of jurisprudence doctrines. This term has been used to describe the age group in transition between childhood and adulthood, which is between ten and fifteen years as found in the study, as for the way adolescents are treated and raised in Islam, the study found that adolescence is a stage of empowerment for children to be adult individuals able to play the required roles in society, and this study is expected to benefit researchers interested in adolescence and all those related to the upbringing of adolescents in general. And Muslim adolescents in particular by treating this group as a group that deserves the empowerment, support and development in the society, not a group that goes through many mental disorders because of which some unacceptable behaviors are justified, Also by relying on the Islamic educational curriculum to promote the positive behaviors of this group and correct their negative behaviors, this study will also pave the way for other future studies that develop educational models based on the Islamic approach in dealing with adolescents, and work to apply it in the field of education. Keywords: adolescence, the Sunnah of the Prophet, empowerment, guidance, Islamic education